The Correlation Between Student’s Reading Habit in English and Students’ Reading Comprehension Ability - Merry Andriani; Ariyanti Ariyanti; arbain arbain (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
Reading comprehension can be influenced by reading habit. This research is intended to identify the students’ ability in reading English. The main objective of this research is to recognize whether there is significant correlation between student’s reading habit in English and students’ reading comprehension ability identified through the use of students’ habit questionnaire and reading test with the text was took from passage in TOEFL test. These subjects who are involved at this research are second semester of English Department in Widya Gama Mahakam Samarinda University. This research used quantitative research method. The research design of this study is correlational study. Reading test and questionnaire were used as the instruments; it was used to find out students reading comprehension (variable Y) and students reading habit (variable X) in order to get the data. Moreover, this research used simple random sampling technique. Population of this research was the second semester of English Department in Widya Gama Mahakam Samarinda. The researcher took 38 students as the sample. In this study the researcher computed the normality test to measure the data have a normal distribution and linearity test to measure the data is linear. The data was analyzed using product moment correlation coefficient by SPSS version 22. The result of this research is 0.657. From the result of this research is 0.657 was higher than the significant degree 0.05 at Sig. (2-tailed). It can be concluded the Null hypothesis (Ho) is rejected and the Alternative hypothesis (Ha) is accepted.